Answer:
the sinθ is 4√17 / 53.6
Step-by-step explanation:
All the steps are on the image :)
An Investment of $10,000 yields 8% interest compounded quarterly. The accumulated capital after 6 months is $10,404. The accumulated capital after 5 years is $14.859.47
From the information given;
- The principal amount of investment = $10,000
- Interest Rate = 8% = 0.08
- number of times it get compounded = 4
a. we are to determine the amount of the accumulated capital after 6 months.
- i.e. when time (t) = 6 months.
Now, using the formula for calculating the amount value of the accumulated capital:
![\mathbf{A = P(1 + \dfrac{r}{n})^{nt}}](https://tex.z-dn.net/?f=%5Cmathbf%7BA%20%3D%20P%281%20%2B%20%5Cdfrac%7Br%7D%7Bn%7D%29%5E%7Bnt%7D%7D)
![\mathbf{A = 10000(1 + \dfrac{0.08\times 1}{4})^{4 \times \frac{1}{2}}}](https://tex.z-dn.net/?f=%5Cmathbf%7BA%20%3D%2010000%281%20%2B%20%5Cdfrac%7B0.08%5Ctimes%201%7D%7B4%7D%29%5E%7B4%20%5Ctimes%20%5Cfrac%7B1%7D%7B2%7D%7D%7D)
![\mathbf{A = 10000(1.02)^2}}](https://tex.z-dn.net/?f=%5Cmathbf%7BA%20%3D%2010000%281.02%29%5E2%7D%7D)
A = $10,404
b. we are to determine the amount of the accumulated capital after 5 years
- i.e. when time (t) = 5 years
![\mathbf{A = P(1 + \dfrac{r}{n})^{nt}}](https://tex.z-dn.net/?f=%5Cmathbf%7BA%20%3D%20P%281%20%2B%20%5Cdfrac%7Br%7D%7Bn%7D%29%5E%7Bnt%7D%7D)
![\mathbf{A = 10000(1 + \dfrac{0.08\times 1}{4})^{4 \times 5}}](https://tex.z-dn.net/?f=%5Cmathbf%7BA%20%3D%2010000%281%20%2B%20%5Cdfrac%7B0.08%5Ctimes%201%7D%7B4%7D%29%5E%7B4%20%5Ctimes%205%7D%7D)
![\mathbf{A = 10000(1.02)^20}}](https://tex.z-dn.net/?f=%5Cmathbf%7BA%20%3D%2010000%281.02%29%5E20%7D%7D)
A = $14859.47
Therefore, we can conclude that the accumulated capital after 6 months is $10,404 and the accumulated capital after 5 years is $14859.47
Learn more about compound interest here:
brainly.com/question/14295570?referrer=searchResults
Answer:
k = 8
Step-by-step explanation:
Since the roots of the equation 3x² + 2x + k are x₁ and x₂ and 2x₁ = 3x₂.
By the roots of an equation, ax² + bx + c , where its roots are x₁ and x₂. It follows that sum of roots are x₁ + x₂ = -b/a and product of roots are x₁x₂ = c/a.
Comparing both equations, a = 3 b = 2 and c = k.
So, x₁ + x₂ = -b/a = -2/3 and x₁x₂ = c/a = k/3
x₁ + x₂ = -2/3 and x₁x₂ = k/3
3x₁ + 3x₂ = -2 (1) and 3x₁x₂ = k (2)
Since 2x₁ = -3x₂, and -2x₁ = 3x₂substituting this into equations (1) and (2) above, we have
3x₁ + 3x₂ = -2 (1) and 3x₁x₂ = k (2)
3x₁ + (-2x₁) = -2 and x₁(3x₂) = k
3x₁ - 2x₁ = -2 and x₁(3x₂) = k
x₁ = -2 and x₁(-2x₁) = k
x₁ = -2 and -2x₁² = k
Substituting x₁ = -2 into -2x₁² = k, we have
-2x₁² = k
-2(-2)² = k
2(4) = k
8 = k
So, k = 8
The answer
to do the calculus, the method is
taking off the paranthesis
adding the term with a similar degree
summing constant terms
(3x^2+3x+5) + (7x^2-9x+8) =
= 3x^2+3x+5 + 7x^2-9x+8
= 3x^2 + 7x^2 + 3x+5 - 9x+8
= 10x² + 3x - 9x +5 +8
= 10x² - 6x + 13
the answer is
(3x^2+3x+5) + (7x^2-9x+8) =10x² - 6x + 13
the error that Lucia did make 3x - 9x = -12x, instead of 3x - 9x = -6x
The next number would be 493